INTEGRATED MANAGEMENT OF SOIL PESTS OF POTATO IN HIGHER HILLS OF HIMACHAL PRADESH - Chandla, V. K.; Chandel, R. S. (Potato Journal, 2013)
Cutworm, Agrotis segetum and white grubs, Brahmina coriacea are the major constraint in potato production in higher hills of Himachal Pradesh. Both cutworm and white grubs are polyphagous pests and cause heavy damage and yield losses to many horticulture crops including potato. So far, great deal of reliance has been put on the chemical control of these pests. To avoid total reliance on pesticides, a carefully designed integrated pest management (IPM) package involving eco-friendly tools with minimum toxicant usage and verification under field conditions is the need of the day. In the present study, eco-friendly IPM schedule was evaluated during 2002 and 2003 seasons in the main potato crop. Seven treatments included were replicated three times in two different sets i.e. potato with garlic as intercrop and potato crop alone, in randomized block design and accommodated in plots measuring 3 m x 2 m. Potato variety Kufri Jyoti was planted during first week of April at 50x20 cm spacing and all the standard agronomical operations were followed while raising the crop. Granular insecticides were applied in furrows while seed tubers were treated with bio-pesticide before planting and foliar sprays were given at the appearance of the pest. Observations were recorded on the per cent plant damage by cutworm in the initial stages of the crop. The data on the damaged tubers by white grubs and yield of marketable potatoes were taken at harvest. The data recorded for two years we statistically analysed. It is revealed from the data that all the treatments proved superior over control in minimizing plant and tuber damage by soil pests. Phorate 10G alone and with garlic as intercrop was found best for the management of cutworm, while chlorpyrifos EC was found superior both against cutworms and white grubs. Bacillus thuringiensis (Bt) and Beauveria bassiana proved effective when applied in combination with garlic and Phorate 10G and it also resulted in maximum marketable tuber yield and benefit/ha. Although synthetic pesticides have been reported as most effective insecticide in reducing plant and tuber damage by soil pests, but in the present studies IPM schedule consisting of bio-pesticides + garlic or bio-pesticide + synthetic pesticide + garlic found equally good and can be suggested as alternate to synthetic pesticide for the management of soil pests in higher hills and getting maximum net benefit/ha.